Effect of Cold Fluid Compensatory Swallowing Combined with Balloon Dilation on the Treatment of Poststroke Cricopharyngeal Achalasia: A Pilot Randomized Controlled Trial. (8th October 2022) - Li, Xiangwei; Jin, Linna; Gu, Chengxiao; Zhang, Wangyuan; Zhou, Xiao; You, Xiaoting
Abstract : Objective . This study is aimed at comparing the treatment efficacy between catheter balloon dilation combined with cold fluid compensatory swallowing training and catheter balloon dilation alone on poststroke cricopharyngeal achalasia (CPA). Methods . We conducted a single-blind, randomized controlled trial (RCT). Poststroke patients with CPA were divided into two groups: the control group (treated with catheter balloon dilation) and the trial group (catheter balloon dilation combined with cold fluid compensatory swallowing). Videofluoroscopic swallowing study (VFSS) was performed, and functional oral intake scale (FOIS) was used to evaluate and compare the swallowing function of patients in the 2 groups before and after intervention. Posttreatment VAS pain scores and recovery time were also measured. Results . VFSS and FOIS scores in the two groups were improved after treatment (P < 0.05 ). In the trial group, VFSS scores in the pharyngeal phase and aspiration degree were significantly higher compared with the control group (P < 0.05 ) but not in the oral phase (P > 0.05 ). The difference in FOIS scores and patients' recovery time from intervention to eating mushy food between the trial and control groups was significant (P < 0.05 ), but not the VAS scores (P > 0.05 ). Conclusion . The catheter balloon dilation combined with cold fluid compensatory swallowing was superior to catheter balloon dilation alone in terms of relieving dysphagia and reducing aspiration in patients with CPA following stroke. Long-term efficacy should be followed up with more objective and quantitative indicators in future studies.